NEW APPROACH TO IMPROVING EDUCATIONAL PROGRAM CONTENT TAKING INTO CONSIDERDATION EMPLOYERS’ REQUIREMENTS - PETROSYAN , HAYK; MATEVOSYAN , MARGARITA (Main Issues Of Pedagogy And Psychology, 2014)
The article presents the issue of regular updating professional education content through improving educational standards and harmonizing them with employment standards. According to the authors, key qualifications serve the basis of professional standards (narrow professional, generalized, urgently functional), a complex of psychological qualities, abilities, knowledge, competences and skills of professionals ensuring effective implementation of certain professional functions. Requirements to the graduates of vocational schools have been studied in the frames of clarifying requirements and professional standards of employment on the results of modernizing educational standards. The results of the studies identify employers’ requirements to graduates, afterwards an organizational–pedagogical model for improving and ameliorating educational programs have been developed.